2015
DOI: 10.1080/07325223.2015.1012916
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Counselor Self-Efficacy Across Academic Training

Abstract: This study investigated counselor self-efficacy and anxiety among psychology students at different levels of training. All participants, including undergraduate and graduate students, completed a set of questionnaires covering topics ranging from clinical experience to feelings encountered during counseling sessions (for example, anxiety and confidence). We compared students across various levels of training and computed a multivariate analysis of variance, with dependent variables measuring self-efficacy, sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 45 publications
0
25
0
2
Order By: Relevance
“…The beliefs that counselors‐in‐training (CITs) hold about their ability to perform as counselors are a fundamental aspect of counselor development (Goreczny, Hamilton, Lubinski, & Pasquinelli, 2015; Larson et al, 1992). Known as counseling self‐efficacy (Larson et al, 1992), a counselor’s belief that he or she will be able to effectively perform counseling‐related tasks in the near future is considered to be “a primary mechanism between simply knowing how to help in a counseling situation and actually executing effective counseling actions” (Greason & Cashwell, 2009, p. 3).…”
mentioning
confidence: 99%
“…The beliefs that counselors‐in‐training (CITs) hold about their ability to perform as counselors are a fundamental aspect of counselor development (Goreczny, Hamilton, Lubinski, & Pasquinelli, 2015; Larson et al, 1992). Known as counseling self‐efficacy (Larson et al, 1992), a counselor’s belief that he or she will be able to effectively perform counseling‐related tasks in the near future is considered to be “a primary mechanism between simply knowing how to help in a counseling situation and actually executing effective counseling actions” (Greason & Cashwell, 2009, p. 3).…”
mentioning
confidence: 99%
“…Previous literature on this relationship has yielded mixed findings. For instance, Goreczny et al (2015) found a relationship between years of experience and counselor self‐efficacy, whereas Larson and Daniels (1998) found the relationship to be minimal. Thus, there is not a clear relationship between years of experience and a sense of efficacy, which is surprising.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety and negative reactions to feedback in counselor training and education is well documented in counseling literature. 23,[45][46][47] Counseling and psychology graduate students demonstrate lowest levels in self-efficacy during the beginning terms of clinical training programs. 47 This is likely due to increased awareness in areas that require growth and exposure to clinical feedback.…”
Section: Discussionmentioning
confidence: 99%
“…23,[45][46][47] Counseling and psychology graduate students demonstrate lowest levels in self-efficacy during the beginning terms of clinical training programs. 47 This is likely due to increased awareness in areas that require growth and exposure to clinical feedback. Students are accustomed to receiving feedback on exams or papers and corrections to these types of work are less likely to be taken personally.…”
Section: Discussionmentioning
confidence: 99%